The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nu14173497
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Indicators of Undernutrition, Infection, and Inflammation in Lactating Women Are Associated with Maternal Iron Status and Infant Anthropometry in Panama: The MINDI Cohort

Abstract: Maternal infections, nutrient deficiencies, and inflammation (MINDI) co-exist in lactating indigenous women in Panama, but their impact on maternal iron status and infant growth is unknown. For this secondary analysis of cross-sectional data of lactating mothers from our MINDI cohort, we investigated associations of MINDI variables with maternal anemia, elevated serum transferrin receptor (sTfR), low serum iron, hepcidin, ferritin, and infant weight-for-age (WAZ), length-for-age (LAZ), and head-circumference-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 91 publications
(125 reference statements)
1
5
0
1
Order By: Relevance
“…The associations of low weight-for-height category and lower folate and vitamin A with both anemia and lower Hb suggest the presence of anemia of undernutrition, mimicking previously reported results in lactating women from the same cohort, where anemia of undernutrition was also evident [ 101 ]. The term ‘anemia of undernutrition’ is used to capture the range of nutritional deficiencies that contribute to anemia, and it encompasses iron and other macro- and micronutrient deficiencies [ 102 ].…”
Section: Discussionsupporting
confidence: 82%
“…The associations of low weight-for-height category and lower folate and vitamin A with both anemia and lower Hb suggest the presence of anemia of undernutrition, mimicking previously reported results in lactating women from the same cohort, where anemia of undernutrition was also evident [ 101 ]. The term ‘anemia of undernutrition’ is used to capture the range of nutritional deficiencies that contribute to anemia, and it encompasses iron and other macro- and micronutrient deficiencies [ 102 ].…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, in the younger age group, taking Fe supplements has been associated with higher odds of experiencing wasting. Similarly, in a study conducted in Panama, supplementing lactating mothers with Fe during the first 6 months of the lactation period was found to be negatively associated with the length-for-age Z score of their children ( 36 ) . This phenomenon is particularly evident in areas with high parasitic infestations, which contribute to childhood undernutrition.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, a study comparing the predictive efficiency of various bone parameters reported that RBP, after alkaline phosphatase and age, was the strongest predictor for BMD in treated postmenopausal osteoporosis [ 23 ]. Similarly, many studies also suggested that RBP may relate to vitamin D by influencing nutrition status [ 24 , 25 ]. As for the relation between RBP and fractures, a study that enrolled the patients with osteoporotic fractures and age-matched control subjects showed that the patients with osteoporotic hip fractures have lower RBP than their controls [ 26 ].…”
Section: Discussionmentioning
confidence: 99%